KEKERASAN SEKSUAL DI LEMBAGA PENDIDIKAN BERDASARKAN PERMENDIKBUD NO. 30 TAHUN 2021 DAN UU TINDAK PIDANA KEKERASAN SEKSUAL TAHUN 2022 - Ika Dewi Sartika Saimima; Noviansyah; Ni Kadek Dian Candra Purnama; I Wayan Arif Yudistira (Abdi Bhara, 2022)
Sexual harassment is a big problem in society and is hidden in most institutions/organizations, and this phenomenon continues to increase as if there is no law to deter it. This activity aims to provide transparent information so that students and educators can understand that there is a particular policy from the government to protect victims of sexual violence in the world of education. The method used in this community service activity is counseling and interactive discussion, using various case examples to facilitate the delivery and acceptance of material. This community service activity is carried out by exploring policies from the government to prevent the impact of sexual violence in educational institutions. The socialization is expected to avoid the risk of students becoming sexual victims by their friends, teachers, and school staff.